Changes in Lactic Acid Bacteria and Quality of Gac Yoghurt Supplemented with Carbohydrate Sources during Chilled Storage - Kulsut, Nirawan; Kapo, Palita; Boonreang, Supot; Panyoyai, Naksit (Indonesian Food Science and Technology Journal, 2022)
Gac yoghurt is formulated by mixing gac juice with cow milk and probiotics to form a thick yellow fluid. The research objective was to study the effect of carbohydrate sources (inulin, honey, sucrose, fruit syrup, and sucrose) on lactic acid bacteria remaining after the chilled storage for 28 days. The gac yoghurt was analyzed with physicochemical and sensory characteristics. The experimental design was a Complete Randomized Design (CRD) with eight parameters (total soluble solids, pH, lactic acid content, syneresis, texture, colour, lactic acid bacteria survival, and sensory evaluation). The results showed that in the presence of honey, gac yoghurt had a higher lactic acid count than other treatments throughout 28 days of storage. The lactic acid growth was observed in the first two weeks, then it was almost constant in the third week and levelled off at the end of storage. The addition of carbohydrates resulted in a lower pH than a control. It increased total soluble solids, titratable acidity, and syneresis effect. Gac yoghurt with inulin enrichment kept for 28 days showed a firmer texture and lighter than the rest. However, sensory results showed that gac yoghurt with sucrose was the most preferred formulae based on the average Hedonic scores followed by the yoghurt fermented with honey, inulin, and fruit syrup, respectively.